“Blessing, not begging” - Banhishikha Ghosh (South Asia Multidisciplinary Academic Journal)
For eons, hijras and kotis of India have survived on socially endorsed livelihoods involving multilayered erotic, ritualistic, cultural, and religious performances. Though a range of structural inequalities preconditioned these livelihoods, the performances serve as a signal to engender, induce, and embolden community expression. Yet these performative acts have continually been disapproved of by the post-colonial Indian state on equating them with the illegal act of begging. Based on field experience and documentary evidence, this paper raises three major issues. First, the performative acts of hijras/kotis should be seen as “blessings,” “ritualistic soliciting,” and “erotic performances,” not as “begging.” Second, ritualistic soliciting is done by choice and represents the longevity of their agency. Third, in the post-COVID-19 period, hijras, kotis, and similar gender nonconforming communities (GNCs) are exposed to unlawful forms of police fining and to an elaborate racket of brokerage systems operated by the ordinary state officials. These acts heighten their embodied vulnerabilities.